2020
DOI: 10.5194/gc-3-203-2020
|View full text |Cite
|
Sign up to set email alerts
|

“Are we talking just a bit of water out of bank? Or is it Armageddon?” Front line perspectives on transitioning to probabilistic fluvial flood forecasts in England

Abstract: Abstract. By showing the uncertainty surrounding a prediction, probabilistic forecasts can give an earlier indication of potential upcoming floods, increasing the amount of time available to prepare. However, making a decision based on probabilistic information is challenging. As part of the UK-wide policy's move towards forecast-based flood risk management, the Environment Agency (EA), responsible for managing risks of flooding in England, is transitioning towards the use of probabilistic fluvial forecasts fo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…For hydraulic design, frequency estimates are often communicated with uncertainty bounds related to sampling uncertainty. However, ensemble forecasts and predictions are not always well understood (Pagano et al, 2014) and decision-making based on probabilistic information is challenging (Arnal et al, 2020).…”
Section: Tackling Challengesmentioning
confidence: 99%
See 2 more Smart Citations
“…For hydraulic design, frequency estimates are often communicated with uncertainty bounds related to sampling uncertainty. However, ensemble forecasts and predictions are not always well understood (Pagano et al, 2014) and decision-making based on probabilistic information is challenging (Arnal et al, 2020).…”
Section: Tackling Challengesmentioning
confidence: 99%
“…1. Obtain stakeholder feedback: We may improve communication strategies by learning about a user's perception of model output (Ramos, Mathevet, Thielen, & Pappenberger, 2010) and by engaging in a dialogue with key players in the decision making process (Addor et al, 2015;Arnal et al, 2020) and public agencies and engineers who develop prediction and modeling tools for operational application. 2.…”
Section: Tackling Challengesmentioning
confidence: 99%
See 1 more Smart Citation
“…The low interest in runoff forecasts can be, to some extent, attributed to the weak communication skills of the hydrologists who develop the service. There are only a few papers (e.g., [50,75]) that put their central focus on communication rather than computational issues. Thus, hydrologists know how to compute forecasts but do not know how to communicate them efficiently.…”
Section: Website Traffic and Demand For Forecastsmentioning
confidence: 99%
“…Flood forecasting in Africa has not received the needed attention in the literature, in spite of the recognized importance of the topic. Although a number of authors (Haile et al 2016;Siddique & Mejia 2017;Huang 2018;Arnal et al 2020;Wenyan et al 2020) have demonstrated the benefit of ensemble forecasts over deterministic forecasts. However, most of the studies that used ensemble forecasting have focused on forecasting for lead times of up to 15 days rather than short-time forecasting (Cloke & Pappenberger 2009;Pagano et al 2014;Emerton et al 2016;Wu et al 2020).…”
Section: Introductionmentioning
confidence: 99%